Economic Impacts of Alternative Regulatory Scenarios on the Florida Fresh Half-Shell Oyster Industry: A Study of Potential Outcomes - Kimberly L. Morgan; T. J. Stevens; Robert L. Degner; Sherry L. Larkin; Charles M. Adams (EDIS, 2010)
FE835, a 3-page executive summary of a report by K.L. Morgan, T.J. Stevens, R.L. Degner, S.L. Larkin, and C.M Adams, summarizes the results of a study to examine the economic impacts of possible closures of the fresh half-shell oyster market for varying time periods with the intention of protecting consumers from Vibrio vulnificus infections. Published by the UF Department of Food and Resource Economics, June 2010.